Justice, Assistance or Charity? What Duties we have toward the World’s Poor? A Preliminary Exploration (Andamios, Revista de Investigación Social, 2014)
In this article I intend to clarify the nature of our duties towards those people living in extreme poverty. Are they duties of justice? Are they duties of assistance? Are they mere charitable, supererogatory actions? I start by critically assessing some of the proposals available in the specialized literature and proceed to suggest three criteria that may orientate us when distributing responsibilities in general. From applying these criteria to the problem of extreme poverty I conclude that we all have duties of justice not to undermine the equal liberty of others to pursue their life plans, duties of justice to support just institutions and duties of assistance to aid those people facing extreme deprivation.
Keywords: Poverty; justice; assitance; perfect duties; agency